The Investigations of PD-Type Fuzzy Logic with Different Polarities Input Shaping for Anti-Sway Control of A Gantry Crane System - Mohd Ashraf, Ahmad; Mohd Syakirin, Ramli; Raja Mohd Taufika, Raja Ismail; Ahmad Nor Kasruddin, Nasir; Mohd Anwar, Zawawi (2009)

(untitled)
This paper presents investigations into the development of PD-type Fuzzy Logic Control with different polarities input shaping for anti-sway control of a gantry crane system. A nonlinear overhead gantry crane system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. To study the effectiveness of the controllers, initially a PD-type Fuzzy Logic Control is developed for cart position control of gantry crane. This is then extended to incorporate input shaper control schemes for anti-sway control of the system. The positive and modified specified negative amplitude (SNA) input shapers with the derivative effects respectively are designed based on the properties of the system. Simulation results of the response of the system with the controllers are presented in time and frequency domains. The performances of the control schemes are examined in terms of level of input tracking capability, swing angle reduction, time response specifications and robustness to parameters uncertainty in comparison to the PD- type Fuzzy Logic control. Finally, a comparative assessment of the amplitude polarities of the input shapers to the system performance is presented and discussed.